Adaptive behavior in autism: Minimal clinically important differences on the Vineland‐II. Issue 2 (21st September 2017) - Chatham, C. H.; Taylor, K. I.; Charman, T.; Liogier D'ardhuy, X.; Eule, E.; Fedele, A.; Hardan, A. Y.; Loth, E.; Murtagh, L.; del Valle Rubido, M.; San Jose Caceres, A.; Sevigny, J.; et al.
Abstract : Autism Spectrum Disorder (ASD) is associated with persistent impairments in adaptive abilities across multiple domains. These social, personal, and communicative impairments become increasingly pronounced with development, and are present regardless of IQ. The Vineland Adaptive Behavior Scales, Second Edition (Vineland‐II) is the most commonly used instrument for quantifying these impairments, but minimal clinically important differences (MCIDs) on Vineland‐II scores have not been rigorously established in ASD. We pooled data from several consortia/registries (EU‐AIMS LEAP study, ABIDE‐I, ABIDE‐II, INFOR, Simons Simplex Collection and Autism Treatment Network [ATN]) and clinical investigations and trials (Stanford, Yale, Roche) resulting in a data set of over 9, 000 individuals with ASD. Two approaches were used to estimate MCIDs: distribution‐based methods and anchor‐based methods. Distribution‐based MCID [d‐MCID] estimates included the standard error of the measurement, as well as one‐fifth and one‐half of the covariate‐adjusted standard deviation (both cross‐sectionally and longitudinally). Anchor‐based MCID [a‐MCID] estimates include the slope of linear regression of clinician ratings of severity on the Vineland‐II score, the slope of linear regression of clinician ratings of longitudinal improvement category on Vineland‐II change, the Vineland‐II change score maximally differentiating clinical impressions of minimal versus no improvement, and equipercentile equating. Across strata, the Vineland‐II Adaptive Behavior Composite standardized score MCID estimates range from 2.01 to 3.2 for distribution‐based methods, and from 2.42 to 3.75 for sample‐size‐weighted anchor‐based methods. Lower Vineland‐II standardized score MCID estimates were observed for younger and more cognitively impaired populations. These MCID estimates enable users of Vineland‐II to assess both the statistical and clinical significance of any observed change. Autism Res 2018, 11: 270–283 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The Vineland Adaptive Behavior Scales (2nd edition; Vineland‐II) is the most widely used scale for assessing day‐to‐day "adaptive" skills. Yet, it is unknown how much Vineland‐II scores must change for those changes to be regarded as clinically significant. We pooled data from over 9, 000 individuals with ASD to show that changes of 2–3.75 points on the Vineland‐II Composite score represent the "minimal clinically‐important difference." These estimates will help evaluate the benefits of potential new treatments for ASD.